(untitled) - Polanyi, Karl (Boston, 1944)
One of the twentieth century's most thorough and discerning historians, Karl Polanyi sheds "new illumination on... the social implications of a particular economic system, the market economy that grew into full stature in the nineteenth century.
Keywords: Kinh tế,Economics; Lịch sử,History